Atmospheric river, a term encompassing different meteorological patterns. (8th September 2021) - Gimeno, Luis; Algarra, Iago; Eiras‐Barca, Jorge; Ramos, Alexandre M.; Nieto, Raquel
Abstract: The study of atmospheric rivers (ARs) and their impacts on extreme precipitation are currently of great research interest in view of their clear socioeconomical implications. However, studies of this type generally contain caveats. The first of these is of a meteorological nature, and is concerned with the diversity of the different meteorological patterns that can be associated in the phenomenological definition, in that there is no guarantee that all so‐called ARs follow the same one. The second concern involves the initial definition of an AR, which implicitly assumes the subtropical origin of the atmospheric moisture that feeds it. To date, it has been observed that in many cases of ARs, most of the moisture originates in regions at higher latitudes. The aim of this article is to open a debate on these two aspects by using well‐known examples of ARs which fit different meteorological patterns, and showing a climatology of the moisture sources that feed ARs. This article is categorized under: Science of Water > Hydrological Processes Science of Water > Water Extremes Abstract : Schematic meteorological configuration (a, b) and vertical cross section (c, d), for two atmospheric rivers (ARs) that landfall on the SE coast of the United States and flow northwards through the Great Plains on May 1, 2010 and July 8, 2010, selected from the database of Guan and Waliser (2015). (a, b) Based on Figures 2 and S1. The ARs are denoted by the blue arrow, and the landfall location is marked by the red filled box. The blue field represents high anomalies of integrated vapor water (IWV) associated with the AR. The yellow arrow marks the position of the wind maximum. Contours in black are mean sea level pressure (MSLP), and L and H are the position of a low level pressure and the anticyclone location. Dark blue, red, and magenta lines around the L in (a) represent the typical cold, warm, and occluded fronts, respectively. Dark green contours are the equivalent thickness at 500/850 hPa. Red filled area is the temperature advection at 500/1000 hPa. The straight magenta line from A to B denotes the positions of the vertical cross sections used in panels below. (c, d) Based on Figures 4 and S2. The red box in the abscissa in each plot marks the point of AR landfall. Contours in black represent the isentropes. The remaining colored contours denote: in shaded blue the relative humidity (moist) content up to 80%, in orange the wind maxima, in green the positive vorticity advection maxima (PVA), in magenta the wind convergence (con) and divergence (div), in red the warm temperature advection (WA), in dashed blue the cold temperature advection (CA), and in light blue the vertical velocity (w).